Clinical Evaluation of a Royal Jelly Supplementation for the Restoration of Dry Eye: A Prospective Randomized Double Blind Placebo Controlled Study and an Experimental Mouse Model. - Sachiko Inoue; Motoko Kawashima; Ryuji Hisamura; Toshihiro Imada; Yusuke Izuta; Shigeru Nakamura; Masataka Ito; Kazuo Tsubota (PLoS ONE)
Background Dry eye is a multifactorial disease characterized by ocular discomfort and visual impairment. Lacrimal gland function has been shown to decrease with aging, a known potent risk factor for dry eye. We have previously found that orally administrated royal jelly (RJ) restored tear secretion in a rat model of dry eye. Methods and findings We examined the effects of RJ oral administration on dry eye in this prospective, randomized, double-blind, placebo-controlled study. Forty-three Japanese patients aged 20-60 years with subjective dry eye symptoms were randomized to an RJ group (1200 mg/tablet, six tablets daily) or a placebo group for 8 weeks. Keratoconjunctival epithelial damage, tear film break-up time, tear secretion volume, meibum grade, biochemical data, and subjective dry eye symptoms based on a questionnaire were investigated at baseline, and at 4 and 8 weeks after intervention. Adverse events were reported via medical interviews. In the RJ group, tear volume significantly increased after intervention (p = 0.0009). In particular, patients with a baseline Schirmer value of ≤10 mm showed a significant increase compared with baseline volume (p = 0.0005) and volume in the placebo group (p = 0.0051). No adverse events were reported. We also investigated the effect of RJ (300 mg/kg per day) administration using a mouse model of dry eye. Orally repeated administration of RJ preserved tear secretion, potentially through direct activation of the secretory function of the lacrimal glands. Conclusion Our results suggest that RJ improves tear volume in patients with dry eye. Trial registration Registered NO. the University Hospital Medical Information Network in Japan (UMIN000014446).